Stents in the femoropopliteal territory: prevalence of fractures and their consequences - DAHER,MARCELO DE AZEVEDO (2020)
ABSTRACT Endovascular treatment for femoropopliteal arterial disease has made revascularization procedures less invasive, but the self-expanding stents used can suffer great wear in arteries with extreme mobility. Objective: to evaluate the prevalence of fractures in stents implanted in the femoropopliteal segment, to identify predisposing factors and consequences on arterial patency. Method: between March and June 2019, thirty patients previously operated for femoropopliteal obstruction underwent stent X-rays in anteroposterior and lateral views to detect fractures and Doppler to analyze arterial patency. Results: we observed 12 cases with fractures (33.3%): 1 type I (2.8%), 3 type II (8.3%), 5 type III (13.9%), 3 type IV (8.3%) and no type V. According to the TASC II we had 1 in group B (8.3%), 6 in group C (50%) and 5 in group D (41.6%) p <0.004. The number of stents per limb was 3.1 (± 1.3) in cases of fracture versus 2.3 (± 1.3) in cases without fracture (p = 0.08). The extension was 274.17mm (± 100.94) in cases of fracture and 230.83mm (± 135.44) in cases without fracture (p = 0.29). On Doppler we had: 17 patients (47.2%) without stenosis, 9 patients (25%) with stenosis> 50% and 10 patients (27.8%) with occlusion (p = 0.37). There was no correlation between fracture and arterial obstruction (p = 0.33). Conclusion: stent fractures are a frequent finding in the femoropopliteal area (33.3%), being more prevalent in cases of more advanced disease (C and D). There was no association between the finding of fracture and arterial obstruction.